An evaluation of the risk of airborne transmission of COVID‐19 on an inter‐city train carriage. (24th October 2022) - Woodward, Huw; de Kreij, Rick J. B.; Kruger, Emily S.; Fan, Shiwei; Tiwari, Arvind; Hama, Sarkawt; Noel, Simon; Davies Wykes, Megan S.; Kumar, Prashant; Linden, Paul F.
Abstract: Experiments were conducted in an UK inter‐city train carriage with the aim of evaluating the risk of infection to the SARS‐CoV‐2 virus via airborne transmission. The experiments included in‐service CO2 measurements and the measurement of salt aerosol concentrations released within the carriage. Computational fluid dynamics simulations of the carriage airflow were also used to visualise the airflow patterns, and the efficacy of the HVAC filter material was tested in a laboratory. Assuming an infectious person is present, the risk of infection for a 1‐h train journey was estimated to be 6 times lower than for a full day in a well‐ventilated office, or 10–12 times lower than a full day in a poorly ventilated office. While the absolute risk for a typical journey is likely low, in the case where a particularly infectious individual is on‐board, there is the potential for a number of secondary infections to occur during a 1‐h journey. Every effort should therefore be made to minimize the risk of airborne infection within these carriages. Recommendations are also given for the use of CO2 sensors for the evaluation of the risk of airborne transmission on train carriages.